Exploring the Influence of Perceived Social Media Marketing Activities on K-Pop Fan Behavior in Indonesia: A Mediation Model in the Entertainment Industry (Study Case Fans of SM Entertainment Artist) - Alfikri Oktavian Yudhistira; Daniel Tumpal Hamonangan Aruan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Social media marketing has become a key strategy for building relationships between brands and consumers. In the entertainment industry especially in K-Pop companies like SM Entertainment actively implement Social Media Marketing Activities (SMMAs) to boost fan engagement and influence purchasing decisions. This study aims to examine the effect of perceived SMMAs on purchase intention, brand loyalty, and impulsive buying among K-Pop fans in Indonesia, while considering the mediating roles of brand trust, brand experience, and brand love. The study focuses on K-Pop fans who are active on social media and interact with promotional content from SM Entertainment’s artists. Data were collected from 316 respondents via an online survey and analyzed using Structural Equation Modeling (SEM) based on the Stimulus–Organism–Response (S-O-R) framework. In this model, SMMAs act as the stimulus, brand trust, brand experience, and brand love serve as the organism, and purchase intention, brand loyalty, and impulsive buying represent the consumer response. The findings show that perceived SMMAs significantly influence brand trust, which in turn enhances brand experience and brand love. These three factors directly and sequentially impact purchase intention, brand loyalty, and impulsive buying. The results emphasize the importance of social media marketing strategies in shaping trust, emotional connection, and meaningful experiences that drive fan behavior. Practically, entertainment companies can use these insights to design more effective and emotionally engaging digital marketing strategies to stay competitive.